From Crisis to Confidence: How Covid-19 Teaching Experiences Transformed Teachers in Cambridge and Edexcel Schools in Dhaka - Rahman, Adneen; Hasan, Md. Mahadhi (JOLLT Journal of Languages and Language Teaching, 2025)
The COVID-19 pandemic forced an unprecedented global shift to online education, compelling teachers to rapidly adapt their pedagogical practices.Â The This study investigates how the COVID-19 teaching experiences transformed English medium school teachers in Dhaka, following the curricula of Cambridge and Edexcel. The study focuses on the challenges, the development of confidence in online teaching tools, and the reshaping of their professional roles and pedagogical approaches. This qualitative research methodology, using teacher narratives, presents the experiences of seven teachers from renowned English medium schools who have shifted to online teaching. The results indicate that teachers encountered considerable obstacles at the outset, such as technological difficulties, insufficient training, and the need to adjust to the dynamics of online classrooms. Nevertheless, as time progressed, their self-assurance increased due to autonomous learning and collaboration with colleagues, resulting in improved digital competence. Additionally, the pandemic transformed their professional roles, fostering a transition from conventional, instructor-focused methodologies to more adaptable, learner-centered strategies. The research emphasizes the need for constant professional development in both technological and emotional aspects of pedagogy. Assuming that the pandemic provided a strong impetus toward lasting changes in teaching methods and teachers' responsibilities, it conforms to new educational trends. This research enhances the understanding of connections between crisis-induced instructional adjustments and their lasting consequences for the teachers' professional development.